Hacking the code ASP.NET web application security - Burnett, Mark M.; Foster, James C. (Rockland, MA : Syngress Publ., 2004)
Hacker Code will have over 400 pages of dedicated exploit, vulnerability, and tool code with corresponding instruction. Unlike other security and programming books that dedicate hundreds of pages to architecture and theory based flaws and exploits, HC1 will dive right into deep code analysis. Previously undisclosed security research in combination with superior programming techniques from Foundstone and other respected organizations will be included in both the Local and Remote Code sections of the book. The book will be accompanied with a FREE COMPANION CD containing both commented and uncommented versions of the source code examples presented throughout the book. In addition to the book source code, the CD will also contain a copy of the author-developed Hacker Code Library v1.0. The Hacker Code Library will include multiple attack classes and functions that can be utilized to quickly create security programs and scripts. These classes and functions will simplify exploit and vulnerability tool development to an extent never before possible with publicly available software. * Learn to quickly create security tools that ease the burden of software testing and network administration * Find out about key security issues regarding vulnerabilities, exploits, programming flaws, and secure code development * Discover the differences in numerous types of web-based attacks so that developers can create proper quality assurance testing procedures and tools * Learn to automate quality assurance, management, and development tasks and procedures for testing systems and applications * Learn to write complex Snort rules based solely upon traffic generated by network tools and exploits.
Includes index.
Keywords: Active server pages -- Security measures; Application software -- Security measures; Computer networks -- Security measures; Electronic books